Mucus Hydration in Subjects with Stable Chronic Bronchitis: A Comparison of Spontaneous and Induced Sputum. (2nd November 2018) - Henderson, Ashley G.; Anderson, Wayne H.; Ceppe, Agathe; Coakley, Raymond D.; Button, Brian; Alexis, Neil E.; Peden, David B.; Lazarowski, Eduardo R.; Davis, C. W.; Fuller, Fred; Almond, Martha; Qaqish, Bahjat; et al.
Abstract: Mucus hydration is important in mucus clearance and lung health. This study sought to test the relative utility of spontaneous sputum (SS) versus the reasonably noninvasive induced sputum (IS) samples for measurement of mucus hydration. SS and IS samples were collected over a 2-day study interval. Sputum was induced with escalating inhaled nebulized 3–5% hypertonic saline. Viscous portions of the samples ("plugs") were utilized for percent solids and total mucin analyses. Cytokines, nucleotides/nucleosides and cell differentials were measured in plugs diluted into 0.1% Sputolysin. Overall, 61.5% of chronic bronchitis (CB) subjects produced a SS sample and 95.2% an IS sample. Total expectorate sample weights were less for the SS (0.94 ± 0.98 g) than the IS (2.67 ± 2.33 g) samples. Percent solids for the SS samples (3.56% ± 1.95; n  = 162) were significantly greater than the IS samples (3.08% ± 1.81; n  = 121), p  = 0.133. Total mucin concentrations also exhibited a dilution of the IS samples: SS = 4.15 ± 3.23 mg/ml ( n  = 62) versus IS= 3.34 ± 2.55 mg/ml ( n  = 71) ( p  = 0.371). Total mucins (combined SS and IS) but not percent solids, were inversely associated with FEV1 percent predicted ( p  = 0.052) and FEV1, /FVC % ( p  = 0.035). There were no significant differences between sample types in cytokine or differential cell counts. The probability of sample collections was less for SS than IS samples. Measurements of hydration revealed modest dilution of the IS samples compared to SS. Thus for measurements of mucus hydration, both SS and IS samples appear to be largely interchangeable.